ESRA19-0639 The ultrasound-guided erector spinae plane block allows opioid free anesthesia in the modified radical mastectomy with axillary dissection: a pilot study about 14 cases. (30th August 2019) - El Ayoubi, S; Ghannam, A; El Ahmadi, B; Belkhadir, Z
Abstract : Background and aims: The modified radical mastectomy with axillary dissection is usually carried out under balanced general anesthesia using opiates, it is a source of moderate to severe postoperative acute pain. Opioid-free anesthesia (OFA) aims to reduce the undesirable effects of opioids while ensuring optimal anesthesia and analgesia perioperatively. We report 14 cases of ultrasound-guided erector spinae plane block (ESPB) to perform surgery using OFA. Methods: We recruited patients presenting no contraindications to the anesthetic technique. the OFA protocol included a general anesthesia with no opioids and an ultrasound-guided ESPB with bupivacaine at T4 level. Prior to incision, patients received a bolus of Ketamine, Ketoprofen, dexamethasone IV. Maintenance of anesthesia was performed by sevoflurane at 1 MAC. In case of haemodynamic repercussions related to nociception, a bolus of fentanyl at 1 μg/kg was administered. Results: After the approval of the ethic committee, we included 14 consenting patients. Hemodynamic variations were all less than 20% of baseline. No patient had any intraoperative opiate injection. Upon waking, patients had a median visual analogical scale (VAS) less than 3. During the first 24 hours, the VAS was less than 3. Only one patient received a bolus of 3 mg morphine IV as part of the catch-up postoperative analgesia. After 24 h, all patients had no resting pain. Conclusions: OFA is used to avoid short-term and long-term adverse effects of opioids, such as: nausea, postoperative hyperalgesia, chronic pain and tumor recurrence. the ESPB allows anesthesia and analgesia in a safe way.